2001
DOI: 10.1038/sj.cdd.4400802
|View full text |Cite
|
Sign up to set email alerts
|

Detection of drug-induced apoptosis and necrosis in human cervical carcinoma cells using 1H NMR spectroscopy

Abstract: Apoptosis and necrosis need to be differentiated in order to distinguish drug-induced cell death from spontaneous cell death due to hypoxia. The ability to differentiate between these two modes of cell death, especially at an early stage in the process, could have a significant impact on accessing the outcome of anticancer drug therapy in the clinic. Nuclear magnetic resonance spectroscopy was used to distinguish apoptosis from necrosis in human cervical carcinoma (HeLa) cells. Apoptosis was induced by treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 25 publications
(24 reference statements)
2
40
0
2
Order By: Relevance
“…Furthermore, in vitro studies have shown that the ratio of the methylene (CH 2 ) lipid resonance (at 1.3 ppm) to the methyl (CH 3 ) resonance (at 0.9 ppm) is correlated to the percentage of apoptotic lymphoblasts after doxorubicin treatment (Blankenberg et al, 1997). This finding was recently confirmed using a human cervical carcinoma HeLa cell system (Bezabeh et al, 2001). In the present study, we found strong ML signals in large, highly necrotic tumours.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, in vitro studies have shown that the ratio of the methylene (CH 2 ) lipid resonance (at 1.3 ppm) to the methyl (CH 3 ) resonance (at 0.9 ppm) is correlated to the percentage of apoptotic lymphoblasts after doxorubicin treatment (Blankenberg et al, 1997). This finding was recently confirmed using a human cervical carcinoma HeLa cell system (Bezabeh et al, 2001). In the present study, we found strong ML signals in large, highly necrotic tumours.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, various reports have suggested that deregulation of AK-B by either knockdown or disruption of the functional kinase domain leads to apoptosis (26,36,69,70). This led us to propose that AK-B combined with EBNA3C would promote resistance to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The early lipid signal changes probably arose from the interactions described recently and occurring between ICEU and the lipid bilayer membranes (Saint-Laurent et al, 2001). The late lipid signal changes (observed after 18 h) may be considered as markers of the apoptotic cascade, therefore reflecting plasma membrane reorganisation and phosphatidylserine externalisation (Blankenberg et al, 1996(Blankenberg et al, , 1997Bezabeh et al, 2001;Brisdelli et al, 2003). Moreover, after the latter stage, there was a decrease in choline that indicates cell death (Blankenberg et al, 1996(Blankenberg et al, , 1997.…”
Section: Discussionmentioning
confidence: 99%
“…For data analysis, each spectrum was phased and baseline-corrected using XWIN-NMR version 2.6 (Bruker software). The resonances were assigned based on the known chemical shifts of the major structural groups and metabolites using published data (Bezabeh et al, 2001;Sitter et al, 2002;Brisdelli et al, 2003) and commercially available pure metabolite reference spectra. The relative content of metabolites was estimated by peak area integration using PeakFit software (version 4, SPSS Science, Chicago, IL, USA).…”
Section: The 1 H-hrmas Nmr Spectroscopy and Data Analysismentioning
confidence: 99%